(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Correlation of GnRH long Agonist protocol and GnRH short Antagonist protocol-quality applying in Assisted Reproductive Technology, we studied which protocol is better to make good quality embryos, oocyte and out come of in-vitro fertilization and embryo transfer. GnRH has important part in manage ovarian stimulation. Effect of GnRH analogous on embryos and oocytes equality. GnRH Antagonist detected successful for ovarian simulation. Oocyte and quality of embryos are very crucial for positive result in in-vitro fertilization.Objectives: The objectives include study of GnRH long Agonist Protocol, Study of GnRH Short Antagonist Protocol and to Correlate it’s Effect on Quality of embryos and oocytes.Methodology: This is invasive methodology giving intra muscular injection in both protocol long Agonist and Short antagonist then we check the follicles size and numbers under USG. Inj HCG given before 34hr of ovum pick up. Oocytes retrieved examined oocyte quality and numbers. Then we will perform ICSI or IVF then check embryos forms and grade in which protocol given good embryos. We transfer embryos blastocyst and morula stage. Β-HCG done after 14 days of embryo transfer.